Inequalities are used to represent unequal expressions
The complete inequality is: [tex]m -6 \ge 5[/tex]
The inequality is given as:
[tex]m + 3 \ge 14[/tex]
Subtract 3 from both sides of the inequality
[tex]m + 3-3 \ge 14-3[/tex]
Subtract 3 from 14
[tex]m + 3-3 \ge 11[/tex]
Subtract 3 from 3
[tex]m \ge 11[/tex]
Next, subtract 6 from both sides of the inequality
[tex]m -6 \ge 11-6[/tex]
Subtract 6 from 11
[tex]m -6 \ge 5[/tex]
Hence, the complete inequality is: [tex]m -6 \ge 5[/tex]
Read more about inequalities at:
https://brainly.com/question/9774970